Polaronic ferromagnetism in conducting polymers - Pereira, E. C.; Correa, A. A.; Bulhões, L. O S; Aleixo, P. C.; Nóbrega, J. A.; De Oliveira, A. J A; Ortiz, W. A. [UNESP]; Walmsley, L. [UNESP] (Elsevier, 2001)
Ferromagnetic behavior at room temperature is reported in metal-free-conducting polymer samples of poly(3-methylthiophene) doped with ClO 4 -. Magnetic moments associated with spin 1/2 positive polarons are possibly interacting through a Dzialoshinski-Moriya anisotropic superexchange via the dopant anions, giving rise to weak ferromagnetism. © 2001 Elsevier Science B.V. All rights reserved.
Keywords: Exchange interactions; Ferromagnetism; Polarons; Polymers; Ferromagnetic behaviors; Poly (3-methylthiophene); Room temperature; Spin 1/2; Superexchanges; Weak ferromagnetism; Conducting polymers; Doping (additives); Magnetic moments; Organic conductors